Fast and Robust Multiqubit Gates on Rydberg Atoms by Periodic Pulse Engineering. Issue 10 (30th August 2022) - Wu, Jin‐Lei; Wang, Yan; Han, Jin‐Xuan; Su, Shi‐Lei; Xia, Yan; Song, Jie; Jiang, Yongyuan
Abstract: The idea of periodic pulse engineering (PPE) is exploited to achieve unconventional Rydberg pumping for a robust multiqubit gate on Rydberg atoms trapped in a 2D array. By designing component parameters in PPE, fast regimes of full and partial Rydberg antiblockade (RAB) among three atoms are explored. Furthermore, through assigning appropriate components in PPE a phenomenon of RAB‐based blockade emerges and then a three‐qubit gate can be achieved. It is identified that two kinds of Rydberg–Rydberg interaction (RRI), van der Waals interaction and dipole–dipole Förster resonance interaction, are both applicative for implementing the proposed scheme. Different from recent schemes of Rydberg atom multiqubit gates, the operated atoms are indistinguishable with respect to the laser field of PPE, and the present one‐step scheme is essentially fast owing to the first‐order dynamics where the dominant component in PPE is not degraded. In addition, the proposed multiqubit gate is robust against atomic decay and deviation of RRI strengths, because the excitation duration of atoms is short, with the total excitation number ⩽1. This work may facilitate experimental demonstration of RAB‐based gates of strongly coupled atoms. Abstract : Unconventional Rydberg pumping is designed by periodic pulse engineering, including fast regimes of full and partial Rydberg antiblockade (RAB), and more importantly RAB‐based Rydberg blockade (RAB‐RB). Different from conventional RB, RAB‐RB is caused by the parameter assignments in components of pulse, and is combined with soft control to account for the imnplementation of the multiqubit gate.